Optimizing the Use of Vegetable Biodigester Fertilizer Using a Website-Based Information System: Optimasi Penggunaan Pupuk Biodigester Sayuran Menggunakan Sistem Informasi Berbasis Website - Ikrom; Yusran; Firmansyah Putra (Journal of Vocational Education and Information Technology (JVEIT), 2026)
IP2MP Sitiung, Dharmasraya Regency processes vegetable waste into biodigester fertilizer (leachate fertilizer), but the fertilization dosage is still determined manually and inaccurately, which risks inhibiting plant growth. This study aims to design a website-based information system to monitor the quality of biodigester fertilizer (pH and voltage) in real time and to optimize the determination of vegetable fertilization dosage. Data were collected through observation, interviews, and document study, while the system was developed using the waterfall model with the PHP programming language, a MySQL database, and sensors based on the NodeMCU ESP8266 microcontroller as the IoT device. The system was designed using Unified Modeling Language (UML), including use case diagrams, activity diagrams, sequence diagrams, and class diagrams, and was subsequently tested using the black box testing method. The results show that the system successfully displays real-time biodigester conditions through the Dashboard page, provides a Dose Calculator feature that automatically calculates fertilizer dose recommendations based on vegetable type and land area, and includes an Activity Logbook feature to record fertilization history. All black box testing scenarios for the admin and general user modules ran according to the expected results, proving that the system is feasible to use and able to improve the efficiency of biodigester fertilizer use compared to manual methods.